Fields, sherds and scholars : recording and interpreting survey ceramics - Meens, Anna; Nazou, Margarita; Put, W. D. J. van de (Leiden : Sidestone Press, 2023)
This book is a significant contribution to the field of survey pottery studies, which is not frequently theorised, and could also serve as a guide and provide inspiration to archaeologists designing their own survey projects and methodologies.Landscape archaeology has heavily relied on pedestrian survey as a field method for more than half a century. In most field projects, archaeological ceramics constitute the lion's share among the finds and the amount of c.
Survey ceramics in the spotlight / Anna Meens, Margarita Nazou and Winfred van de Put -- Pottery studies in survey in the eastern Mediterranean over the last 20 years : a personal account / Kristina Winther-Jacobsen -- Statistical distances on a map (STADION) : a method for exploring intra-site variability of pottery assemblages / Jesús García Sánchez -- Diagnostic visibility and problems of quantification in survey assemblages : examples from the Mazi Archaeological Project (Northwest Attica) / Christian F. Cloke, Alex R. Knodell, Sylvian Fachard and Kalliopi Papangeli -- Down to the details : the pottery recording methodology from the Kea Archaeological Research Survey / Margarita Nazou, Joanne Murphy, Natalie Abell, Shannon LaFayette Hogue and John Wallrodt -- The potential of impasto pottery studies for understanding regional settlement dynamics, cultural transmission and connectivity in Bronze Age landscapes in Italy / Francesca Ippolito and Peter Attema -- Survey, ceramics and statistics : the potential for technological traits as chronological markers / Ayla Krijnen, Jitte Waagen and Jill Hilditch -- The analytical potential of intensive field survey data : developments in the collection, analysis and interpretation of surface ceramics within the Pontine Region Project / Tymon de Haas and Gijs Tol -- The Ayios Vasileios Survey Project : diagnostic samples versus total samples and their biases / Corien W. Wiersma -- Diagnosing the undiagnostic : using sherd databases as a source of interpretation / Vladimir Stissi -- Tales of two cities : urban surveys of the Hellenistic and Roman cities of Sikyon and Knossos / Conor P. Trainor and Peter J. Stone -- A case in point(s) : the Late Hellenistic to Late Roman pottery from extra-mural Tanagra and the formation of the surface record : methodology, chronology and function / Dean Peeters, Philip Bes and Jeroen Poblome -- Buried landscapes and landscapes of the buried : considering rural burial in survey / Anna Meens -- List of authors.
Includes bibliographical references (pages 162-164).
Description based on online resource; title from digital title page (ProQuest Ebook Central, viewed on November 13, 2024).
eBooks on EBSCOhost
Keywords: Pottery -- Analysis; Pottery, Ancient; Archaeology -- Methodology; Archéologie -- Méthodologie.